PENGARUH KREDIBILITAS MICRO-INFLUENCER TERHADAP MINAT BELI PRODUK SKINCARE LOKAL SOMETHINC DENGAN SIKAP MEREK SEBAGAI VARIABEL MEDIASI (Studi pada Pengguna Media Sosial TikTok di Kota Semarang) - Dimas Putra Harwansya; Mahfudz Mahfudz (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to determine and analyze the effect of the credibility dimensions, namely the attractiveness, expertise, and trustworthiness of micro-influencers on purchase intention of Somethinc skincare products with brand attitude as a mediating variable. This study used a purposive sampling technique to collect data. Data was obtained by distributing questionnaires to 110 individuals who use social media TikTok, domiciled in the city of Semarang, and have seen at least three promotional contents for the Something skincare product by micro-influencers on social media TikTok. The method used in this research is Structural Equation Modeling (SEM) using AMOS 26.0 program. The results of the study showed that micro-influecer’s credibility dimensions namely attractiveness has an insignificant effect on brand attitude but expertise and trustworthiness have positive and significant effect on brand attitude. Other result shows that brand attitude has positive and significant effect on purchase intention.